Respond or Dismiss: Interactions That May Support Loving, Bullying and Solitude in Mathematics - Andersson, Annica; Wagner, David (Journal of the Canadian Association for Curriculum Studies, 2019)
We develop an analytical frame to support reflection on how love, bullying and solitude appear in communication in mathematics classrooms. The frame distinguishes among communication acts that are responsive or dismissive to others, and identifies how the acts draw on authority to open or close dialogue. Our examination of high school students’ language repertoires revealed that their communication acts influence both their development of mathematics and their interpersonal relationships. To illustrate the framework in use, we draw on transcripts from group interactions in one high school mathematics class. We consider how the particular kinds of communication acts may support and develop caring, antagonism or reclusion. The illustrative analysis illuminates the complexity of human relationships—how communication acts in mathematics classrooms intertwine personal autonomy, interpersonal positioning, and how these communication acts are intertwined with interpersonal positioning.